PHARMACOECONOMIC MODELING OF ANTIRETROVIRAL DRUGS USE DURING TREATMENT OF HIV INFECTION - V. A. Chibilyaev; A. Yu. Kulikov; R. I. Yagudina (Фармакоэкономика)
Comparative pharmacoeconomic analysis of two therapeutic strategy (the strategy A and the strategy B), which differ with the expansion of access to ART was conducted using deterministic model. The aim of this research was to optimize the therapy of HIV-infected people and determine the most effective therapeutic strategy. On the basis of obtained epidemiological data model determines the advantages of therapeutic strategy with higher access to ART (strategy B). In particular, the results of simulation showed that the application of ART allows to significantly reduce new HIV infections and deaths related to the virus. Use of ART allows to optimize the costs, the value of quality-adjusted life year (QALY) is growing, which makes it advisable to use ART in health care on larger scale.